Joining of Ramor 500 Steel by Submerged Welding and its Examination of Thermal Analysis in ANSYS Package Program - Taskaya, Semih; Gur, Ali Kaya; Orhan, Ayhan (Elsevier, 2019)
ANSYS is a simulation software program used in the engineering fields. This program is used after the modeling phase and allows to test in the virtual, i.e. program, environment before the prototype is generated. Simulation of the welded structure is one of the most important subjects of the studies conducted on welding process. In this study, the complex situations encountered in the welded structures are tried to be solved with the help of computers by using Ansys finite elements method and numerical analysis and mathematical models. After the submerged welding; mechanical properties of the samples were investigated by using tensile test and SEM weld metal fracture surface. SEM-XRD analyses were carried out for the structures of the samples which showed characteristic in the weld metal. The fracture surfaces of the samples of the welded joints subjected to tensile test were investigated by using SEM and thus the fracture type was determined. Thermal analyses were performed by generating the model of the welded joints in ANSYS packaged software. In terms of the intensity of the joints, 250 A were found to have full intensity at all joints. As a result of the studies, it was determined that the results of the experimental studies and the results of the finite element solutions were compatible with each other.
Keywords: Ramor 500; ANSYS; Submerged welding; Thermal analysis